Do audit firms derive higher fees from increased client satisfaction? - Tan, Shirley Sher Lee. (2008)
The study investigates if higher client satisfaction and peceived auditor reputation lead to higher audit fees. Client satisfaction was found to be insignicant while auditor reputation was significant.